Coping with Covid-19: The case of the National Library of Jamaica. Issue 2 (August 2020) - Lashley, Beverley; Graham, Nicholas; Prawl, Nicole
While Asian and European countries were grappling with the Covid-19 pandemic, the first imported case from the United Kingdom surfaced in Jamaica on 10 March 2020. The article will trace the steps taken by the National Library of Jamaica (NLJ) before and during the pandemic while improving the value of our cultural heritage to Jamaica and the wider diaspora. The NLJ celebrated 40 years of sterling contribution to the development of Jamaica from March 1979 to April 2020. It has been a leading voice in the region in disaster management and preparedness. Through its Preservation and Conservation Branch, and oversight from the Disaster Preparedness Committee, the NLJ has become a training ground for professionals in the information and conservation field. While highlighting the work of the NLJ, the article will also present statements and surveys conducted on regional and international bodies. These organisations include the Association of Caribbean University, Research and Institutional Libraries (ACURIL), the Community of Directors of National Libraries (a subgroup of the International Federation of Library Associations (IFLA) and the Society of American Archivists. The surveys conducted gleaned a greater appreciation of the impact of Covid-19 on libraries and archives regionally and internationally. The article will address other pandemic crises that have affected Jamaica. It will also demonstrate that being proactive and prepared for viral episodes can mitigate the risks. The NLJ used the opportunity to facilitate service delivery while being socially distant from its patrons.